Assessing the feasibility of increasing spatial resolution of remotely sensed image using HNN super-resolution mapping combined with a forward model - Minh, Nguyen Quang (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 4, 2012)
Abstract: